The Role of Extracellular Vesicles as a Shared Disease Mechanism Contributing to Multimorbidity in Patients With COPD - Laura V. Reid (Frontiers Media S.A., 2021)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. Individuals with COPD typically experience a progressive, debilitating decline in lung function as well as systemic manifestations of the disease. Multimorbidity, is common in COPD patients and increases the risk of hospitalisation and mortality. Central to the genesis of multimorbidity in COPD patients is a self-perpetuating, abnormal immune and inflammatory response driven by factors including ageing, pollutant inhalation (including smoking) and infection. As many patients with COPD have multiple concurrent chronic conditions, which require an integrative management approach, there is a need to greater understand the shared disease mechanisms contributing to multimorbidity. The intercellular transfer of extracellular vesicles (EVs) has recently been proposed as an important method of local and distal cell-to-cell communication mediating both homeostatic and pathological conditions. EVs have been identified in many biological fluids and provide a stable capsule for the transfer of cargo including proteins, lipids and nucleic acids. Of these cargo, microRNAs (miRNAs), which are short 17-24 nucleotide non-coding RNA molecules, have been amongst the most extensively studied. There is evidence to support that miRNA are selectively packaged into EVs and can regulate recipient cell gene expression including major pathways involved in inflammation, apoptosis and fibrosis. Furthermore changes in EV cargo including miRNA have been reported in many chronic diseases and in response to risk factors including respiratory infections, noxious stimuli and ageing. In this review, we discuss the potential of EVs and EV-associated miRNA to modulate shared pathological processes in chronic diseases. Further delineating these may lead to the identification of novel biomarkers and therapeutic targets for patients with COPD and multimorbidities.